A systematic review of frailty education programs for health care professionals. (7th July 2022) - Warren, Nicola; Gordon, Emily; Pearson, Ella; Siskind, Dan; Hilmer, Sarah N.; Etherton‐Beer, Christopher; Hanjani, Leila Shafiee; Young, Adrienne M.; Reid, Natasha; Hubbard, Ruth E.
Abstract: Objectives: To identify and examine the reported effectiveness of education programs for health professionals on frailty. Methods: A systematic review was conducted of articles published up to June 2021, examining the evaluation of frailty training or education programs targeting health professionals/students. The participant demographics, program content and structure, effectiveness assessment methodology and outcomes, as well as participant feedback, were recorded with narrative synthesis of results. Results: There were nine programs that have evaluated training of health professionals in frailty. These programs varied with respect to intensity, duration, and delivery modality, and targeted a range of health professionals and students. The programs were well‐received and found to be effective in increasing frailty knowledge and self‐perceived competence in frailty assessment. Common features of successful programs included having multidisciplinary participants, delivering a clinically tailored program and using flexible teaching modalities. Of note, many programs assessed self‐perceived efficacy rather than objective changes in patient outcomes. Conclusions: Despite increasing attention on frailty in clinical practice, this systematic review found that there continues to be limited reporting of frailty training programs.